Taking on High-Density Lipoprotein Cholesterol and Triglycerides - Buckley, Rita (MD Conference Express, 2013)
Dyslipidemia plays a critical role in cardiovascular (CV) risk. Strong evidence supports that lower low-density lipoprotein cholesterol is better, but there are more questions than answers on what to do about triglycerides (TG) and high-density lipoprotein cholesterol (HDL-C). This article discusses high TGs and HDL-C, emerging CV disease risk factors, as well as novel therapeutic strategies for plasma lipid disorders.